Effect of Anovulation and Subclinical Endometritis on Fertility of Lactating Dairy Cows: Why Are Dairy Cows Not Getting Pregnant—Lack of Cyclicity, Uterine Disease, or Both? - Klibs N. Galvão; Achilles Vieira-Neto (EDIS)
Virtually all Holstein dairy cows have the first wave of follicle growth starting two weeks postpartum, with about 30% of these cows ovulating within 21 days in milk. This 3-page fact sheet presents the results of a recent paper that evaluated the individual and combined effects of anovulation and subclinical endometritis on reproductive performance of dairy cows. Written by Klibs N. Galvão and Achilles Vieira-Neto, and published by the UF Department of Veterinary Medicine-Large Animal Clinical Sciences, May 2014.